Istirātījiyyah Mahārah al-Istimāʿ fī Taʿlīm al-Lughah al-ʿArabiyyah li al-Nāṭiqīn bi Ghairihā, al-Kitāb al-Asāsiy bi Maʿhad al-Khurṭūm al-Dauliy Namūżajan - Nahla Hasan (Rumah Jurnal IAIN Bukittinggi, 2022)
The article dealt with the strategies of listening skills and their acquisition for non-native Arabic language learners through the introductory book at the Khartoum International Institute for the Arabic language at the intermediate level. The study intends to know the strategies used in implementing the listening skill as one of the primary and practical skills in teaching language and communication with others, and the listening skill has elements that are not based only on receiving audible sounds and understanding the meanings of words and sentences. Instead, it requires using the senses of sight and hearing together besides the mind. To achieve this, the researcher followed the following methodological and procedural steps: The study tool is: the interview and attendance of three lectures for listening lessons at the Khartoum International Institute, and directing interview questions to the two teachers in the second semester of the year 20/2021 AD. The number of learners was between twenty-five to thirty learners from countries: Indonesia, Nigeria, China, Comoros, and others. The study relied on the descriptive approach based on observation, induction, and analysis. It is carried out according to several strategies, including direct and indirect.تناولت المقالة إستراتيجية مهارة الاستماع وإكسابها لمتعلمي اللُّغة العربية الناطقين بغيرها من خلال الكتاب الأساسي، بمعهد الخرطوم الدولي للغة العربية المستوى المتوسط، بهدف معرفة الإستراتيجية المستخدمة في تنفيذ مهارة الاستماع بكونها من المهارات الأساسية والفاعلة في تعليم اللُّغة والاتصال مع الاَخرين، ولمهارة الاستماع عناصر لا تستند فقط إلى استقبال الصوت المسموع وإدراك معاني الكلمات والجمل؛ بل تتطلب استخدام حاستي البصر والسمع معًا بجانب العقل، من أجل تحقيق ذلك اتبعت الباحثة الخطوات المنهجية والإجرائية الآتية: أداة الدِّراسة هي: المقابلة وحضور ثلاث محاضرات للدروس الاستماع بمعهد الخرطوم الدولي، وتوجيه أسئلة المقابلة للمعلمتين في الفصل الدراسي الثاني للعام 20/2021م، أمّا بالنّسبة للمتعلمين، فقد انحصر عددهم ما بين خمس وعشرين إلى ثلاثين متعلما، من دول: إندونيسيا، ونيجيريا، والصين وجزر القمر، وغيرها، اعتمدت الدِّراسة على المنهج الوصفي القائم على الملاحظة والاستقراء والتحليل، وتوصلت الدِّراسة إلى نتائج من أهمها: أنّ تدرس